2016
DOI: 10.1039/c5ta08386a
|View full text |Cite
|
Sign up to set email alerts
|

Micro–mesoporous iron oxides with record efficiency for the decomposition of hydrogen peroxide: morphology driven catalysis for the degradation of organic contaminants

Abstract: A template-free solid-state synthesis of a highly organized and morphologically controlled iron(iii)oxide micro–mesoporous Fenton catalyst is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 41 publications
0
28
0
Order By: Relevance
“…The MMIO catalyst was characterized by field‐emission scanning electron microscopy (FESEM), high‐resolution transmission electron microscopy (HRTEM), XRD, N 2 adsorption–desorption isotherm measurements, and Mössbauer spectroscopy . The FESEM image of iron oxide is depicted in Figure a, which shows the intact flower‐shaped morphology clearly.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The MMIO catalyst was characterized by field‐emission scanning electron microscopy (FESEM), high‐resolution transmission electron microscopy (HRTEM), XRD, N 2 adsorption–desorption isotherm measurements, and Mössbauer spectroscopy . The FESEM image of iron oxide is depicted in Figure a, which shows the intact flower‐shaped morphology clearly.…”
Section: Resultsmentioning
confidence: 99%
“…The MMIO catalystw as characterized by field-emission scanning electron microscopy (FESEM), high-resolution transmission electron microscopy (HRTEM), XRD, N 2 adsorption-desorption isotherm measurements, and Mçssbauer spectroscopy. [17] The FESEM image of iron oxide is depictedi nF igure 1a,w hich shows the intact flower-shaped morphology clearly.T he MMIO catalystc omprises several nanorods and shows nanosized particles (5-7 nm), which indicatest he ultrafine building units of 3D nanocomposites (Figure 1b). The lattice fringes of randomly oriented grains support and indicate the crystallinen ature of the MMIO catalyst.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that ferrous oxalate with microporous and mesoporous structure has been prepared, and the porous structure brings a relatively large specific surface area [20]. At present, it is rarely reported about the application of micro-mesoporous ferrous oxalate to supercapacitors while ironic oxide is well known active materials.…”
Section: Introductionmentioning
confidence: 99%